Submissive Behaviour and Depression: A Case-Control Study Done at Tertiary Care Centre in Jaipur - Yadav, Abhilasha; Kamra, Arvin (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2019)
Background: The construct of submissive behaviour and its association with psychopathology especially with depression has been explored extensively in western countries but in India literature on this subject is conspicuous by its absence.Objectives: This article explores the phenomenon of submissive behaviour and its correlation with depression.Materials and Methods: This study was conducted at Psychiatric Centre Jaipur (SMS Medical College, Jaipur) on OPD basis from July, 1998 to December, 1999. This was a case control study, 50 matched subjects with age range 15-60 years were included in study and control group. Study Group consisted of 50 depressed patients as per ICD-10 criteria (F32 and F33), controls were selected from general population randomly and were free from any psychiatric illness. Beck depression inventory and Submissive behaviour scale were used in the study.Statistical Analysis: Mean, Standard deviation, Student ‘t’ test, Pearson’s correlation co-efficient were used to analyse the data.Results: Mean submissive behaviour score of study group was 27.76 and control group was 11.46, the difference between these scores in study and control group was found to be statistically significant. There was positive correlation between depression BDI scores and submissive behaviour scores at r=+0.2875.Conclusion: This research shows that submissive behavior is an important construct in relation to depression even in Indian population. However, further research is needed to support the findings of this study in Indian depressives.